The Blank Votes as Valid Votes in Regional Election Counting: A Constitutional Law Perspective - Nanda Friska Dewita; Hikam Hulwanullah (Fakultas Hukum Universitas Wahid Hasyim, 2025)
This study examines the recognition of blank votes as valid votes in Indonesia’s regional elections from a constitutional law perspective. Using a normative approach, the research analyzes the legal framework and implications of Constitutional Court Decision No. 100/PUU-XIII/2015. The findings reveal that recognizing blank votes strengthens democratic legitimacy, enhances voter sovereignty, and functions as a corrective mechanism against oligarchic party practices. However, regulatory gaps remain regarding procedures when blank votes prevail. The study recommends reformulating electoral norms to ensure consistency, transparency, and legal certainty in regional elections.